Synchronicity of nociceptive and non-nociceptive adjacent neurons in the spinal dorsal horn of the rat: stimulus-induced plasticity - Eblen-Zajjur, Antonio Alejandro; Sandkühler, Jürgen (Neuroscience, 1996)
Current knowledge of spinal processing of sensory information is largely based on single-cell recordings; however, temporal correlation of multiple cell discharges may play an important role in sensory encoding, and single electrode recordings of several neurons may provide insights into the functions of a neuronal network. The technique was applied to the lumbar spinal dorsal horn of pentobarbital-anaesthetized rats during background activity, steady-state noxious heat stimulation (48°C, 100s), cold block spinalization or radiant heat-induced inflammation of the skin, and the recordings were evaluated by means of auto-correlation, autospectral and cross-correlation analysis. Background patterns obtained by these three methods were extremely stable in time. Autocorrelation with short lag peaks was observed in 72.2% of neurons (n=223). Background correlated discharges were found in 83.6% of the neuron pairs (n=134). Cross-correlation with a central peak, suggestive of common input to the recorded cells, was the most common pattern observed in almost all laminae and was associated with high incidence (91.8%) of overlapping receptive fields and with neurons with initial peak autocorrelation pattern. Cross-correlations with central trough were associated with increase autocorrelation patterns. Bilateral peaks in cross-correlation, suggestive of reverberating circuitry, were observed only for pairs of neurons located in laminae IV and V and were associated with rhythmic discharges in one or in both simultaneously-recorded neurons. Lagged peaks or troughs were observed in 4.6% and 2.2% of neuronal pairs, respectively. Long-lasting skin heating induced qualitative changes (pattern changes) in the cross-correlation of 21.6% of the neuron pairs and quantitative changes in 85.7% of them. During skin inflammation qualitative changes in the cross-correlation pattern were observed in 30.8% of the neuron pairs, and quantitative changes (strength and/or synchronization time) in about 57.7% of them. Spinalization induced quantitative changes in cross-correlation in the vast majority of neuron pairs. The results of the present study suggest that discharges of neighbouring spinal dorsal horn neurons are strongly synchronized probably by propriospinal and primary afferent sources. The existence of functional reverberating circuitry was also evidenced. Finally, the functional synchronicity in the spinal dorsal horn presents stimulus-induced plasticity which consists mainly of changes on the strength and/or time of the synchronization and rarely of activation of new connectivities.
Online 15 October 1997
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 04.05.2021